Crystal field ground state of the orthorhombic Kondo semiconductors CeOs-2Al-10 and CeFe-2Al-10 - Strigari, Fabio; Hu, Zhimin; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2013)
Here we present linear-polarization-dependent soft x-ray absorption spectroscopy data at the Ce M4,5 edges of CeOs2Al10 and CeFe2Al10. Despite the strong hybridization between 4f and conduction electrons and the existence of spin gaps as seen in inelastic neutron scattering, we were able to determine the crystal field ground state wave functions by combining our spectroscopy data with magnetization measurements. The results quantitatively explain the small ordered moment along c and the measured magnetic moment along the easy a axis in CeOs2Al10.
Die Ziffern bzw. Zahlen 2 und 10 im Titel sind tiefgestellt
Gesehen am 27.09.2017